2020
DOI: 10.1590/0037-8682-0504-2019
|View full text |Cite
|
Sign up to set email alerts
|

Importance of microenvironment to arbovirus vector distribution in an urban area, São Paulo, Brazil

Abstract: Introduction: The study of the landscape ecology, biological microhabitat, and epidemiological implications for the distribution of the main vectors Aedes aegypti and Aedes albopictus contribute to the prevention and control actions regarding the diseases they transmit. Methods: This study sought to assess data on positive properties of the vector control program activities from 1998 to 2010. An entomological survey was also carried out on a sample of buildings collecting larvae and pupae from containers betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…With the exception of Acre state, the presence of Aedes albopictus has been reported in all states of Brazil (Saraiva et al 2019;Ferreira-de-Lima et al 2020). Its spread in urban areas and its important capacity as a vector of arboviruses have been monitored in several studies (Arduino et al 2020;Honorio et al 2019;Melo Ximenes et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of Acre state, the presence of Aedes albopictus has been reported in all states of Brazil (Saraiva et al 2019;Ferreira-de-Lima et al 2020). Its spread in urban areas and its important capacity as a vector of arboviruses have been monitored in several studies (Arduino et al 2020;Honorio et al 2019;Melo Ximenes et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These contrasts reveal that the study of the determinants of the occurrence of virus infections transmitted by mosquitoes of Aedes genus is very complex, especially in urban centres with co-circulation of three of these agents (DENV, CHIKV and ZIKV), as occur in FSA since 2015 [13]. Possibly it is due to factors inherent to the receptivity of the physical environment [29] and socioeconomic conditions [30,31], beyond other factors involved, such as, the existence of competition between different agents for the vector, the possibility of co-infection in humans and mosquitoes [32] and the vector control measures adopted in each specific space [33].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…aegypti and Ae. albopictus 34 . The large number of eggs deposited on the gel of the OH and OG traps demonstrated that the hydrated SAP stimulated the deposition of eggs directly on the hydrogel ( Figure S5 ).…”
Section: Discussionmentioning
confidence: 99%
“…aegypti and Ae. albopictus for more than 20 years 34 , and has experienced annual epidemics of dengue and, more recently, the circulation of Zika and chikungunya viruses.…”
Section: Methodsmentioning
confidence: 99%